Use of Social Media in Building Brand Identity Among Young Entrepreneurs - Yuwono, Imam (KnE Social Sciences, 2023)
Increasing the number of social media users is a potential for entrepreneurs or young entrepreneurs, especially to develop their businesses on social media. The business world has a potential target of 191 million active social media users. Optimum utilization of social media for business can benefit business people and improve their welfare and the people involved, such as expanding employment opportunities to contribute to community welfare and reduce poverty. One effort that can be made is to build a brand identity on social media by young entrepreneurs. As it is well known, social media users in Indonesia, especially Instagram, are young people. The large number of young entrepreneurs doing business on social media is a challenge in itself to be able to compete to attract the attention of consumers; therefore, the products offered must have an identity so that they are easily recognized among competitors. The research method used is descriptive; the research subjects are young entrepreneurs who had used social media for business for at least 1 year and were selected purposively. Keywords: brand identity, social media, young entrepreneurs